Padronização e validação de um teste imunoenzimático quantitativo anti-SARS-CoV-2 - Silva, Danilo Nobre da (2022)
Since the declaration of the SARS-CoV-2 virus as responsible for causing the COVID-19 pandemic in 2020, several efforts have been initiated and continue to be made towards control, diagnosis and therapeutic management. Immunochromatographic and immunofluorescence (FIA) tests were developed based on the qualitative investigation of antibodies against SARS-CoV-2 and recommended to investigate the prevalence of the infection. However, many of them have low sensitivity and specificity. However, the quantitative serological test used in the diagnosis of numerous infections, the enzyme-linked immunosorbent assay (ELISA), has high sensitivity, specificity and reproducibility, which may be a more suitable test for diagnosis, monitoring of the evolution of COVID-19 and response to immunization. The objective of this work was to standardize and validate an in-house quantitative enzyme immunoassay for the diagnosis and follow-up of COVID-19. Initial tests were performed on samples from patients with COVID-19 to standardize the technique and later validate it. First, the standardization of the steps of the immunoenzymatic assay was carried out. Afterwards, the standard curve, the cut off, and the tests for the test validation were determined. For statistical analysis, the significance level of p<0.05 was considered. The cut off was determined by the mean concentration of CN (3.59ng/mL) obtained in March/2019, before COVID-19, plus two standard deviations. cut off=11.49ng/mL. At validation, the assay had 53% sensitivity and 94% specificity compared to FIA. Considering that the FIA kit used is a qualitative test, the precision of this serological assay was evaluated because it presented a high number of false negatives among the samples studied, and a comparison with another test was considered. Another analysis was performed with the anti-RBD-S1 neutralizing antibody test and resulted in 94% sensitivity and 91% specificity. Recombinant protein N was selected in this work for its high antigenicity and immunogenicity, functional multipotentiality, relationship with viral pathogenesis, and that most immunoenzymatic tests currently marketed are based on studies with the spike protein. The in-house quantitative indirect anti-IgG immunoenzymatic assay for SARS-CoV-2 is a technically simple and fast test, with better yield and results that are easy to read and interpret. Contrary to most commercial serological tests currently with qualitative methodologies, this test has the advantage of being a quantitative test, providing more robust results and with greater specificity. The application of this assay provides important information for the diagnosis, therapeutic management and monitoring of the recovery of patients with COVID-19 and, consequently, for planning the epidemiological control of the disease. Thus, the indirect quantitative enzyme immunoassay was standardized and validated for the detection of anti-SARS-CoV-2 IgG antibodies, then determining the adequate concentration of the antigen, the primary and secondary antibody dilutions, the cut off and the standard curve, generating a new test of high quality, high sensitivity, high specificity and low cost.